Regulation of intracellular membrane trafficking and cell dynamics by syntaxin-6. Issue 4 (28th May 2012) - Jung, Jae-Joon; Inamdar, Shivangi M.; Tiwari, Ajit; Choudhury, Amit
Abstract : Intracellular membrane trafficking along endocytic and secretory transport pathways plays a critical role in diverse cellular functions including both developmental and pathological processes. Briefly, proteins and lipids destined for transport to distinct locations are collectively assembled into vesicles and delivered to their target site by vesicular fusion. SNARE (soluble N -ethylmaleimide-sensitive factor-attachment protein receptor) proteins are required for these events, during which v-SNAREs (vesicle SNAREs) interact with t-SNAREs (target SNAREs) to allow transfer of cargo from donor vesicle to target membrane. Recently, the t-SNARE family member, syntaxin-6, has been shown to play an important role in the transport of proteins that are key to diverse cellular dynamic processes. In this paper, we briefly discuss the specific role of SNAREs in various mammalian cell types and comprehensively review the various roles of the Golgi- and endosome-localized t-SNARE, syntaxin-6, in membrane trafficking during physiological as well as pathological conditions.